Safety and tolerability of azilsartan medoxomil in subjects with essential hypertension: a one-year, phase 3, open-label study. (17th February 2016) - Handley, Alison; Lloyd, Eric; Roberts, Andrew; Barger, Bruce
Abstract: This 56-week phase 3, open-label, treat-to-target study, involving 2 consecutive, non-randomized cohorts, evaluated the safety and tolerability of azilsartan medoxomil (AZL-M) in essential hypertension (mean baseline blood pressure [BP] 152/100 mmHg). All subjects ( n = 669) initiated AZL-M 40 mg QD, force-titrated to 80 mg QD at week 4, if tolerated. From week 8, subjects could receive additional medications, starting with chlorthalidone (CLD) 25 mg QD (Cohort 1) or hydrochlorothiazide (HCTZ) 12.5–25 mg QD (Cohort 2), if required, to reach BP targets. Adverse events (AEs) were reported in 75.9% of subjects overall in the two cohorts (73.8% Cohort 1, 78.5% Cohort 2). The most common AEs were dizziness (14.3%), headache (9.9%) and fatigue (7.2%). Transient serum creatinine elevations were more frequent with add-on CLD. Clinic systolic/diastolic BP (observed cases at week 56) decreased by 25.2/18.4 mmHg (Cohort 1) and 24.2/17.9 mmHg (Cohort 2). These results demonstrate that AZL-M is well tolerated over the long term and provides stable BP improvements when used in a treat-to-target BP approach with thiazide-type diuretics.